Micropropagação de espécies de fisális com potencial econômico - Silva, Luciana Sabini da (2020)
In vitro cultivation techniques, such as micropropagation, have been considered promising tools for the production of quality seedlings on a large scale. The objective of this work was evaluate asepsis protocols, composition and concentration of culture media in the in vitro establishment of physalis species. Four experiments were conducted in vitro. In experiment I, seeds of 3 species of physalis (Physalis peruviana, P. ixocarpa and P. minima) were used x 3 asepsis protocols (I = Twin 20 solution for 5 minutes + 70% alcohol for 30 seconds + sodium hypochlorite for 3 minutes, II = 70% alcohol for 30 seconds + sodium hypochlorite for 3 minutes, III = 70% alcohol for 3 minutes + sodium hypochlorite for 10 minutes). For 30 days, fungal and bacterial contamination and the percentage of germination were evaluated every 4 days. In experiment II, 3 culture media (MS, Knudson and WPM) and explants 3 species of fisális (Physalis peruviana, P. ixocarpa and P. minima) were used. In experiment III, explants of 2 species of physalis (Physalis peruviana and P. minima) x 4 concentrations of MS culture medium (0, 50, 75 and 100%) were used. In experiment IV, explants of 2 species of physalis (Physalis peruviana and P. minima) x 4 sucrose concentrations (0, 15, 30 and 60 L-1) were used. For experiments II, III and IV after 30 days were evaluated: number of seedlings, shoots, leaves and roots, length of the largest root (cm) and aerial part of plant (cm), fresh and dry seedling biomass (g). The experimental design was completely randomized, in a 3 x 3 (experiments I and II) and 2 x 4 (experiments III and IV) factorial scheme, containing 5 repetitions, 1 glass per repetition and 5 seeds per glass. Protocols II and III were appropriate for P. peruviana germination, and I and III for P. minima, the three protocols were efficient for controlling fungi and bacteria. Sucrose concentrations close to 50 g L-1 favored the establishment of P. peruviana of approximately 20 g L-1 favored the establishment of P. minima. The culture medium MS is the most suitable for the in vitro establishment of P. peruviana, P. minima and P. ixocarpa. The culture medium at 100% concentration obtained better values in the in vitro development parameters evaluated for the species P. peruviana and P. minima.